Combined orthodontic-surgical approach in the treatment of impacted upper canines - Ivanović Dragan; Tomić Slavoljub; Davidović Lado; Nogo-Živanović Dajana; Ivanović Tanja (Serbian Medical Society - Dental Section, Belgrade, 2019)
Impacted tooth is the tooth that failed to reach occlusal level, with a growth of 2/3 of the root completed. Etiological factors of the impacted teeth are various, but the main reason is the lack of space for their eruption. The most common impacted teeth are lower wisdom teeth, then upper wisdom teeth, upper canines and lower premolars. A seventeenyear-old patient referred by a general dentist came to the clinic for an orthodontic examination. The existence of upper primary canines on both sides was revealed by clinical examination. After ortopantomography analysis, the impacted upper canines were diagnosed. The treatment plan was the extraction of primary teeth, surgical exposure of impacted teeth and orthodontic treatment using fixed orthodontic appliance. The orthodontic treatment of impacted teeth achieved excellent results. The success depends on adequate planning and teamwork of orthodontist and oral surgeon.